(untitled) (Lembaran Ilmu Kependidikan, 2024)
The difficulties in reading experienced by students are due to students not knowing letters or not being proficient in reading as well as students’ lack of inspiration regarding the general atmosphere, so teacher efforts are needed to develop students’ reading literacy skills. The aim of this research is to describe the teacher’s efforts to develop reading literacy skills in class I students at SD Negeri 105 Pekanbaru. This research design is qualitative with a case study type. The subjects in this research were school principals, teachers and students. Data collection techniques and instruments use observation, interview and documentation techniques. Testing the validity of the data in this study used data triangulation techniques. The data analysis method used is in accordance with the Miles and Huberman theory which has stages, namely data reduction, data presentation and drawing conclusions. The results of the research show that there are three teacher efforts in developing the reading literacy skills of grade 1 students at SD Negeri 105 Pekanbaru, namely carrying out a school literacy program by getting into the habit of carrying out reading activities for 20 minutes which are routinely carried out once a week in the school yard, providing interesting learning media and collaborate with students’ parents. The novelty in this research is the teacher’s efforts to develop reading literacy by involving collaboration between parents and teachers with the Nyalanesia movement.